2013
DOI: 10.1186/1471-2334-13-557
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of Aggregatibacter actinomycetemcomitansinfection in patients with cerebral infarction and diabetic renal failure: a cross-sectional study

Abstract: BackgroundRecent epidemiological studies suggest that periodontitis is a major risk factor for renal failure and cerebral infarction. The aim of this study was to evaluate the association among periodontitis, renal failure, and cerebral infarction, focusing on microbiological and immunological features.MethodsTwenty-one patients treated with hemodialysis (HD) were enrolled in this study. They were 8 with diabetic nephropathy and 13 with non-diabetic nephropathy. Blood examination, periodontal examination, brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
(42 reference statements)
1
8
0
5
Order By: Relevance
“…There was no cross‐reactivity with other inflammatory mediators. IgG antibodies against P. gingivalis and A. actinomycetemcomitans were also analyzed by ELISA as described previously 21 …”
Section: Methodsmentioning
confidence: 99%
“…There was no cross‐reactivity with other inflammatory mediators. IgG antibodies against P. gingivalis and A. actinomycetemcomitans were also analyzed by ELISA as described previously 21 …”
Section: Methodsmentioning
confidence: 99%
“…There are many studies on the general prevalence of periodontitis summarized by Kassebaum et al [ 21 ], and there are a few studies concerning the possible association between chronic dental infection and stroke [ 22 , 23 ], but to the best of our knowledge, there are no other studies on the association between these infections and subarachnoid haemorrhage. In the present study, we showed that deep periodontal inflammatory pockets and periapical lesions were more common in patients with a cerebral aneurysm than in the normal population.…”
Section: Main Textmentioning
confidence: 99%
“…There has been a significant interest in the possible association between oral and systemic diseases in the past few decades [ 27 29 ], especially after the case-control study by Mattila et al [ 30 ] who noticed a significant association between poor dental health and acute myocardial infarction in the patients, as compared to control subjects. Subsequently, various epidemiological studies have investigated and supported a causal association of periodontitis with several clinical systemic diseases, including cardiovascular disease [ 31 , 32 ], diabetes [ 33 ], respiratory disease [ 34 ], adverse pregnancy outcomes [ 35 ], Alzheimer's disease [ 36 ], pancreatic cancer [ 37 ], and cerebral infarction [ 38 ]. In addition to the chronic inflammation triggered in response to the oral pathogens, periodontal infection may also result in tooth loss, oral pain, poor mastication, and several nutritional defects and may also be expected to be related with Alzheimer's disease and dementia [ 39 41 ].…”
Section: Periodontal Infections and Other Systemic Diseasesmentioning
confidence: 99%